EFFECTS OF BLUEBERRIES ON INFLAMMATION, MOTOR PERFORMANCE, AND COGNITIVE FUNCTION - Shukitt-Hale, B. (Innov Aging, 2017)
Motor and cognitive function decrease with age, to include deficits in balance, coordination, gait, processing speed, executive function, memory, and spatial learning. These functional declines may be caused by long term increases in and susceptibility to oxidative stress and inflammation. Research conducted in our laboratory, initially with aged animals but more recently with humans, has shown that consumption of blueberries, which are high in polyphenolics and have antioxidant and anti-inflammatory properties, can prevent and even reverse age-related neuronal deficits. Participants, aged 60–75 years, in a randomized, double-blind, placebo-controlled trial, consumed freeze-dried blueberry (24g/d, equivalent to 1cup blueberries) or placebo, and completed a battery of motor and cognitive tests at baseline, and following 45 and 90 days of intervention. Blueberry supplementation improved some aspects of performance and berry serum metabolites were able to reduce inflammatory stress signals in a cell model. Therefore, dietary interventions with blueberries may be one strategy to forestall or even reverse age-related neuronal deficits.